Advanced Password Stealers: Muhammad Arslan Tariq - Tariq, Muhammad Arslan (International Journal for Electronic Crime Investigation, 2019)
People have access to everything available online and uses services given by others that also brings a great amount of risks. Everyone has something which is valuable to him, he wants to keep it private from others and uses password to protect it. A Password may be of any kind. But there are also some people who are intruders and wants to steal others passwords for different purposes. This research paper is regarding the study of password hackers/stealers. Let’s discuss about the passwords Stealers types malicious persistent programs and key loggers. some embedded drivers with these programs and some case scenarios where hackers have been successful in stealing information, even now a days where modern world has done tremendous achievement regarding information security issue why these hackers have been so successful? In this paper, we will also share some tips to save ourselves from such hackers and in this paper, we will try to clarify the difference between spyware key loggers and other password stealers.